Sing YouTube Subtitled Video of Native Speaker to Enhance Speaking Ability and Cultural Understanding - *, Riyani (Proceeding of International Conference on Teacher Training and Education, 2016)
The objective of the research was to find out whether the use of YouTube Video could enhance studentsâ speaking ability and cultural understanding. The research method used was Classroom Action Research. The subject of the research was beginner Indonesian students at Northern Illinois University (NIU) in the academic year of 2014/2015. There were sixteen students in this class. They were all American and they had never learned Bahasa Indonesia (Indonesian Language) before. They first took Indonesian class in Fall semester 2014. The lack of exposure to Indonesian in the U.S. made the students difficult to speak in Indonesian and to know Indonesian culture. In Spring semester 2015, the researcher regularly used videos of Indonesian Native speakers from YouTube during teaching and learning process. The video also provided the idea about Indonesian culture. To facilitate comprehension of the video, the researcher developed an assortment of supporting materials, such as listening comprehension questions, glossaries, and follow-up discussion questions. Some of the videos were very funny and entertaining, which were enjoyed by almost everyone and particularly favored in culture. Finding from the research revealed that the use of video from YouTube could get students energized and engaged in the hands-on learning process. Students got more time to enhance their listening comprehension and to practice their speaking skill at the same time. They were interested in and involved in the discussion about Indonesian culture from the videos. It was clearly an instructional medium that was compelling and generated a much greater amount of interest and enjoyment than the more traditional printed material.